2019
DOI: 10.1038/s41598-019-40589-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Mean Platelet Volume on Local Advanced Non-Small Cell Lung Cancer Managed with Chemoradiotherapy

Abstract: Mean platelet volume (MPV), the most commonly used measure of platelet size, and is altered in patients with malignancies. The aim of this study was to investigate the effect of MPV on overall survival (OS) of patients with locally advanced (Stage IIIA/B) inoperable non-small cell lung cancer (NSCLC). This retrospective study included patients who received concomitant chemoradiotherapy (CCRT) with cisplatin + etoposide regimen due to locally advanced stage IIIA/B NSCLC. The study included a total of 115 cases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“… 3 The complicated interactions between activated platelets and cancer cells lead to tumour growth, aberrant angiogenesis, invasion and metastasis. 4–6 A mounting body of evidence suggests that MPV plays an important prognostic role in various types of tumours, including upper gastrointestinal tumours, 7–14 colorectal cancer, 15 16 lung cancer, 17–19 breast cancer 20–22 and urothelial carcinoma. 23 24 However, the association between MPV level and cancer prognosis has not been comprehensively investigated due to the inevitable heterogeneity of the samples in different studies.…”
Section: Introductionmentioning
confidence: 99%
“… 3 The complicated interactions between activated platelets and cancer cells lead to tumour growth, aberrant angiogenesis, invasion and metastasis. 4–6 A mounting body of evidence suggests that MPV plays an important prognostic role in various types of tumours, including upper gastrointestinal tumours, 7–14 colorectal cancer, 15 16 lung cancer, 17–19 breast cancer 20–22 and urothelial carcinoma. 23 24 However, the association between MPV level and cancer prognosis has not been comprehensively investigated due to the inevitable heterogeneity of the samples in different studies.…”
Section: Introductionmentioning
confidence: 99%
“…Lung adenocarcinoma (LUAD), the most frequent subtype of lung cancer, has increased both in incidence and mortality[2]. Though traditional treatments, such as radiotherapy, chemotherapy and radical surgery, have been used clinically, the prognosis is still poor with a 5-year survival rate below 15%[3, 4]. Currently, patients cannot receive timely treatment because there is no effective early diagnostic method[5].…”
Section: Introductionmentioning
confidence: 99%
“…PDW, MPV, and P-LCR are often used to measure platelet size and as surrogate markers of platelet activation (31). Several studies have reported that high PDW and MPV were poor prognostic markers in various malignancies (32)(33)(34). P-LCR is often reported as a prognostic factor in coronary artery disease and myocardial infarction, but has never been associated with cancer prognoses (35).…”
Section: Discussionmentioning
confidence: 99%